Trade and geography: Paul Krugman and the 2008 nobel prize in economics - Steven Brakman; Harry Garretsen (Center for Economic Studies and ifo Institute (CESifo), 2009)
The 2008 Nobel prize for economics was awarded to Paul Krugman for three papers -Krugman (1979, 1980, 1991). In this paper we illustrate that, indeed, these three papers are closely connected. We present - a summary of - the papers using a unified framework. Central in the discussion is the so-called home market effect that was already alluded to in Krugman (1979). We evaluate his work and conclude that these three papers changed and improved the way economists think about trade and geography.
Keywords: F1; N7; 330; Neue ökonomische Geographie; Home Bias Puzzle; Theorie